2021
DOI: 10.7759/cureus.19768
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sofosbuvir and Velpatasvir Combination for the Treatment of Chronic Hepatitis C in Patients With or Without Cirrhosis

Abstract: Background and aim For years, interferon-based treatment has been offered to patients with chronic hepatitis C virus (HCV) infection; however, the complexity of the treatment, efficacy, and adverse effects were the primary concerns. All these concerns were addressed with the introduction of directly acting antivirals (DAAs) to treat chronic HCV. Sofosbuvir and velpatasvir are second-generation DAAs used in combination for the treatment of chronic HCV infection. The aim of our study was to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The impact of male sex on the odds of response to DAA therapies, including the SOF/VEL option, has been evaluated in numerous RWE analyses supporting our findings. 11, [40][41][42] Finally, the list of factors that reduce the chances of successful SOF/VEL therapy established in the current study is closed by a failure of previous treatment. Adding it to the combination of previously-described negative predictors lowered the cure rate to 67%.…”
Section: Results Characteristics Of the Study Populationmentioning
confidence: 81%
“…The impact of male sex on the odds of response to DAA therapies, including the SOF/VEL option, has been evaluated in numerous RWE analyses supporting our findings. 11, [40][41][42] Finally, the list of factors that reduce the chances of successful SOF/VEL therapy established in the current study is closed by a failure of previous treatment. Adding it to the combination of previously-described negative predictors lowered the cure rate to 67%.…”
Section: Results Characteristics Of the Study Populationmentioning
confidence: 81%
“…Results of our study was comparable to the studies conducted in past. [23,24] Comorbidities were hypertension found in 37 (55.2%) cases, diabetes in 15 (22.4%), ischemic heart disease in 10 (14.9%) cases and 5 (7.5%) patients. [21][22][23][24] Our research demonstrated sofosbuvir and velpatasvir to be extremely efficient against chronic HCV in 94.03%.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] Comorbidities were hypertension found in 37 (55.2%) cases, diabetes in 15 (22.4%), ischemic heart disease in 10 (14.9%) cases and 5 (7.5%) patients. [21][22][23][24] Our research demonstrated sofosbuvir and velpatasvir to be extremely efficient against chronic HCV in 94.03%. In a study by Wong et al in Asia, individuals with chronic hepatitis C had a 99.5% SVR rate with sofosbuvir and velpatasvir with or without ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of current research showed comparable outcomes to the previous studies. [18,19] Efficacy of sofosbuvir and velpatasvir with or without ribavirin in patients with chronic hepatitis C was investigated at 99.5 percent by Wong et al in Asia, but only 88 percent by patients with decompensated cirrhosis, according to the research. SVR patterns were found to be comparable to those seen in our research [20].…”
Section: Discussionmentioning
confidence: 99%